Crisis in digital era and brand sustainability: Analyzing the #whitelabapologize activism on social media - Chasana, Rona Rizkhy Bunga; Purworini, Dian; Apriliani, Riski (Jurnal Komunikasi, 2025)
This research aims to examine how crisis information spreads on social media and leads to activism. The public perceives the Whitelab brand event, which collaborated with K-Pop idol Sehun, as fraught with issues. This has resulted in public protests and the emergence of the #whitelabapologize hashtag on Twitter. This qualitative research uses social network analysis (SNA) to understand the social network and actors surrounding the conversation. A total of 10,000 tweets using #whitelabapologize were extracted from Twitter using Netlytic on the crucial date of the event. The research results classify #whitelabapologize as hashtag activism. Individual actors and the fan bases of K-pop idols drive the conversations on this social network. The data also reveals that this activism follows the logic of connective action.